Building resilient Arctic science amid the COVID-19 pandemic - Andrey N. Petrov (Nature Portfolio, 2020)
Arctic research faces unprecedented disruptions due to COVID-19. This ‘pause’ gives an opportunity to reflect on the current state and the future of Arctic science and move towards a more resilient, thus equitable, coordinated, safe and locally-embedded Arctic research enterprise. Arctic science has been greatly affected by COVID-19. This comment looks forward to how Arctic science could be conducted in the future.